Strategic Development Security (PPS): Efforts to Prevent Corruption by the Attorney General's Office - Maulani, Indah; Setiyawan, Wahyu Beny Mukti; Mantri, Bagus Hanindyo (VJJ, 2021)
This research aims to describe the efforts made by the Strategic Development Security (PPS) in the prevention of corruption which is based on a qualitative doctrinal approach. Therefore in this study prioritizes secondary data collected by literature study. The data that has been processed is then analyzed qualitatively. Based on the research results, it was found that the efforts made by the Strategic Development Security Program (PPS) could be done by providing legal information; hold a discussion or discussion together; provide legal information and legal counseling and the Attorney General's Office can also involve other agencies or parties that have the capacity, competence and relevance to legal information materials.